Synthesis of α-LiFeO2/Graphene nanocomposite via layer by layer self-assembly strategy for lithium-ion batteries with excellent electrochemical performance. (15th October 2020) - Hu, Youzuo; Zhao, Hongyuan; Tan, Ming; Liu, Jintao; Shu, Xiaohui; Zhang, Meiling; Liu, Shanshan; Ran, Qiwen; Li, Hao; Liu, Xingquan
Abstract: As a potential alternative cathode material, α-LiFeO2 suffers a realization handicap, mainly due to its poor electrical conductivity and low lithium ion diffusion rate. In this work, we have successfully synthesized α-LiFeO2 /rGO nanocomposite through a layer by layer self-assembly modification process and annealing treatment. Due to the strong electrostatic attraction between opposite charged spices, α-LiFeO2 nanoparticles were homogeneously dispersed on the graphene sheet to form a typical interconnected conducting network which was beneficial for electronic conductivity and ionic diffusivity. In comparison to pristine α-LiFeO2, the α-LiFeO2 /rGO displayed an excellent electrochemical performance with average discharge capacities of 238.9, 187.2, 178.4, 121.8 and 99.5 mA h g −1 at 0.1, 0.2, 0.5, 1 and 2 C, respectively. Besides, the specific capacity retained 164.9 mA h g −1 and 107.98 mA h g −1 after 50 cycles at 0.5 C and 1 C, respectively. The remarkable progress in rate capability and cycling ability of this new nanocomposite developed a new approach to improve the electrochemical performance of α-LiFeO2 .